MONITORING GERAKAN SHALAT MELALUI KAMERA DENGAN METODE POSE PREDICT - astriani; Nyatu Latifah; Iskandar Lutfi (Universitas Islam Balitar Blitar, 2022)
Worship is a spiritual activity that is routinely carried out as a form of respect to God, this worship itself has various forms and ways to do it, one of which is prayer where this prayer is an activity of respecting God and also praying. This prayer also has several requirements and procedures that must be followed such as doing purification or self-cleaning by doing ablution then reading intentions and prayers during the prayer process, etc.To facilitate the worship process, efforts have been made to assist humans in the worship process such as reminding prayer times and also helping to inform worship activities. But as humans there will always be new problems, one of which is memory because humans have a condition where the brain is overworked so humans experience a state of forgetting or not remembering something. This tools using webcam as input data and the computer portable or laptop to process the image and show the output text, to detect the pose this tools using mediapipe library to helping object detection.